Perkembangan Penelitian Akuntansi Keperilakuan: Berbagai Teori dan Pendekatan yang Melandasi - Ataina Hudayati (Jurnal Akuntansi dan Auditing Indonesia)
This paper aims at explaining the development of the behavioral accounting research based on articles from empirical research in the area of management accounting. The discussion focuses on the development of the approaches prevailed and various theories underlying these researches. More specifically, this paper explains changes of approaches, initially used normative approach and then tends to shift to be more descriptive. Moreover, it is also explained further changes of the approach from initially based on universalistic approach to be contingency approach. The author also describes the development of this behavioral accounting research based on various underlying theories, such as Attribution Theory, Expectation Theory, Goal Theory, and Agency Theory.